Socio-Political Prpblems of Black Muslims in the USA: Past and Present - Ben bordi, Sad Laib, Lina kholoud (Univesity of El-Oued, 2022)
يمثل المسلمون الأمريكيون من أصل أفريقي أكبر مجموعة عرقية في الولايات المتحدة الأمريكية. بالرغم من ذلك واجهوا العداء ضد السود بالإضافة الى مجموعة متنوعة من المشاكل الاجتماعية و السياسية و المالية و العرقية. تهدف هذه الدراسة إلى البحث في المشكلات الاجتماعية والسياسية للمسلمين السود في أمريكا في الماضي والحاضر. علاوة على ذلك، يسلط الأضواء على التمييز العنصري و العرقي ضد الجالية الأمريكية من أصل أفريقي و أهم أسبابه. يتبنى هذا البحث تحليل وصفي تاريخي للمعطيات المتاحة لغرض تقديم صورة واقعية عن حالة الامريكين من أصل إفريقي بالإضافة إلى دراسة المشاكل الاجتماعية و السياسية التي تواجههم في أمريكا. بعد تحليل الأنواع المختلفة من المشاكل العنصرية والاجتماعية والسياسية التي يتعرض لها الأمريكيون من أصل أفريقي توصلت نتائج البحث إلى أن المسلمين السود يعرضون للتمييز العنصري بسبب لون بشرتهم ودينهم ، وهي النتيجة النهائية للدراسة. African-American Muslims represent the largest ethnic group in the United States of America. They faced anti-Black hostility, in addition to a variety of social, political, financial and ethnic problems. The study under investigation aims to depict the socio-political problems of Black Muslims in America in the past and present. It also traces the reasons behind the racial and ethnic discrimination against the African American community. It examines the treatment of the white community toward the Black Muslim community. The study condected a historical and descriptive analysis of the existing literature to provide a realistic image of the African American experience in America as well as reveal the imperfection of the American system. After analyzing the various types of racism, social and political, which African Americans are exposed to, the results concluded that Black Muslims are exposed to racial discrimination because of their skin color and religion, which is the study's ultimate outcome.
Keywords: African-American Muslims, Discrimination, Political Problems, Religion, Social Poblems; المسلمون الأمريكيون من أصل أفريقي ، تمييز ، مشاكل سياسية ، دين ، مشاكل اجتماعية